Behaviour of H-section purlin connections in resisting progressive collapse of roofs. (15th December 2019) - Yan, Shen; Rasmussen, Kim J.R.; Liu, Xinlu; Dai, Liusi; Zhao, Xianzhong
Highlights: Conduct tests to study bridging capacity of purlin connection following local damage of roof. Investigate collapse-resisting mechanisms and failure modes of purlin connection. Propose theoretical model to predict slip of bolts in purlin connection. Propose component-based model to obtain full-range behaviour of purlin connection. Abstract: When a truss roof is subjected to sudden local damage, purlins are capable of bridging the damaged truss unit, thereby increasing the robustness of the integrated roof system. To investigate the bridging capacity purlins can provide, experiments were carried out on bolted fin plate connections that join thin-walled H-section purlins to the main truss, investigating their behaviour under a main truss-removal scenario. Eight specimens with varied connection details were tested. Results of all experiments are provided in detail, including the full-range vertical resistance versus displacement curves, the collapse-resisting mechanisms, and the failure modes, being either bolt shear failure or combined bolt bearing and net-section tensile failure. Experimental results showed that better bridging capacity can be achieved by adopting relatively larger diameter bolts, reducing the bolt group height, applying higher preloading force when installing bolts, and increasing the end distance for the bolt holes. Meanwhile, a theoretical model is proposed to predict the vertical resistance versus displacement response of the purlin-to-connection assembly. This model is capable of capturing the slip of bolts, and the gradual yielding and failure of the connection components, and thus gives predictions that are in reasonably good agreement with the experimental results.